Effects of the transcatheter closure of atrial septal defect on electrocardiographic and echocardiographic parameters six months after the closure - (:unkn) unknown (My University, 2017)
0

Although percutaneous transcatheter atrial septal defect (ASD) closure (TCC) has been performed on adults for a long time there is limited data about the effects of the procedure in the literature and the majority of studies have been performed on children. The study purposed to evaluate the impact of TCC on cardiac remodeling, electrical changes and exercise capacity in adults. Transthoracic echocardiography and electrocardiography were performed one day before and six months after TCC in 27 consecutive patients who underwent successful TCC. Twenty-seven age and sex matched healthy subjects were used as control group. Right ventricular (RV) diameter (had decreased from 44±6.3 to 34±3.9; p<0.001), right atrial (RA) diameter (had decreased from 38±5.6 to 34±4.7; p<0.001), systolic pulmonary artery pressure (sPAP) (had decreased from 38±5.1 to 32±4.3; p<0.001) and P dispersion (Pd) times (had decreased from 59±9.9 to 45.2±16.3; p<0.001) significantly decreased in patients with ASD after TCC. However, these parameters obtained after TCC were still higher compared with parameters of healthy controls. There were not significant differences regarding QT dispersion (QTd) times between ASD patients before and after TCC and healthy controls. New York Heart Association (NYHA) functional class of patients with ASD was significantly improved after TCC. The findings of the present study indicate that although TCC leads to significant improvements regarding right heart dimensions and sPAP and Pd values of ASD patients; residual deterioration still persists up to 6 months after the procedure
Keywords: Genel ve Dahili Tıp